2016
DOI: 10.1007/s00432-016-2196-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of genetic variants involved in immune checkpoints in patients with colorectal cancer

Abstract: In conclusion, this results suggest that the genetic predisposition of the host may affect the anti-tumor immune reaction in CRC. The results of this study may also be helpful when selecting targets for novel drug development to promote the anti-tumor immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Yoon S et al . identified that PD‐1 rs10204525 has an influence on the survival outcomes of the patients with respectable CRC . Sasaki H et al .…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Yoon S et al . identified that PD‐1 rs10204525 has an influence on the survival outcomes of the patients with respectable CRC . Sasaki H et al .…”
Section: Discussioncontrasting
confidence: 77%
“…16 Yoon S et al identified that PD-1 rs10204525 has an influence on the survival outcomes of the patients with respectable CRC. 23 Sasaki H et al showed that rs36084323 in the PD-1 GG genotype was correlated with a poor survival of patients of nonsmall-cell lung cancer. 24 However, in our study, the SNPs in PD-1 were not found to be associated with GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many other studies have proved associations of rs187084 and rs352140 with numerous immune-related diseases, response to therapies, as well as bacterial and viral infections in populations of both Western and Eastern Eurasian ancestry [20,21,22,23,24,25]. It is also worth noting that the common rs4586 SNP, flanking the promoter of CCL2 gene, which appeared significant for genotype frequencies between our cases and controls (p = 0.0079, OR = 8.5, Table II), was recently found to be significantly correlated with anti-tumour immune reaction in Korean patients with colorectal cancer [26] and associated with the clinical outcome in Japanese individuals with locoregional gastric cancer [27]. Moreover, the TLR2 intergenic polymorphism rs4585282 (previous rs numbers: rs6535939, rs61329579), which was found in our study as significant for genotype frequencies (at p = 0.0000033 or p = 0.0083, depending on the model of association, Table II), was recently indicated as displaying modest associations with some vitiligo subgroups [28], while the T allele of this SNP was previously reported to be associated with pulmonary tuberculosis in a West African but not a European population sample [29].…”
Section: Resultsmentioning
confidence: 55%
“…Interestingly, repeated infusion of recombinant sCD5 protein into wild-type mice reproduced both the immunophenotypic changes and the exacerbated anti-melanoma response, thus ruling out that they could be attributed to putative transgenesis artifacts. From another point of view, genetic variants of immune checkpoint regulators may influence the outcome of cancer patients [64][65][66]. Very recently, two retrospective studies have reported the relevance of nonsynonymous CD5 single nucleotide polymorphisms (rs2241002 C>T, P224>L; rs2229177 C>T, A471>V) in solid and non-solid tumors outcome.…”
Section: Cd5 In Cancer Immunotherapymentioning
confidence: 99%